Breve historia de la secretaría de interpretación de lenguas - Cáceres Würsig, Ingrid (Meta, 2004)
AbstractThe article traces the history of the Secretaría de Interpretación de Lenguas (Language Interpreting Secretariat), which was created by Charles V in 1527 to support the Consejo de Estado (Council of State) and which can be considered as a pioneering organization in Europe in the field of “official” translation. Here we can find also the origin of the sworn translation in the Iberian Peninsula. At the same time and from the 18th century so-called traductores de Estado (State translators) started to work directly for other state offices, whose activity is also described. At the end of the 18th century a new figure emerges, namely the joven de lenguas (jeunes de langues), which can be considered as the first step in the development of the diplomatic career. More specifically, the following main questions will be answered: When and why was an official translation and interpreting service first created in Spain? What was its incumbent? Who worked for this service and how did applicants enter the office? Which languages and what type of documents were translated? How were these linguistic services remunerated?